The Role of Biotechnology in Plant Breeding for Sustainable Agriculture in Brazil - Ika Chandriyanti; Yunita Sopiana; Eny Fahrati (Techno Agriculturae Studium of Research, 2024)
Research Background: Sustainable agriculture is increasingly becoming a global priority, including in Brazil, which is one of the major producers of agricultural commodities. Biotechnology in plant breeding has provided an important solution to increase plant productivity and resistance to pests, diseases, and extreme environmental conditions. Research Objectives: This study aims to explore the role of biotechnology in crop breeding in Brazil and its impact on sustainable agriculture. Research Method: This study uses a qualitative descriptive approach with case study analysis on major crops such as soybeans, corn, cotton, and sugarcane. Data were collected through interviews with farmers and biotechnology experts as well as literature analysis. Research Results: The results show that the application of biotechnology increases plant productivity by up to 30%, as well as strengthens plant resistance to pests and climate change. However, the adoption of this technology is still limited to large commodities, with uneven access among smallholders. Research Conclusion: Biotechnology plays an important role in supporting sustainable agriculture in Brazil, but efforts are needed to expand access to these technologies so that more farmers, including small-scale ones, can take advantage of them. Supportive policies and adequate infrastructure are needed to accelerate the adoption of biotechnology across Brazil's agriculture